1987
DOI: 10.1161/01.str.18.3.575
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid pattern of red blood cell membranes and risk of ischemic brain infarction: a case-control study.

Abstract: The fatty add composition of red blood cell membranes (which reflects dietary fat intake) was studied in 28 male patients with recent (<3 days) ischemic stroke and 56 matched controls. Fifteen fatty acids were measured by means of chromatographic analysis. Percentages of linoleic, 22:5, and 22:6 acids were significantly lower in red blood cell membranes of stroke patients than in those of matched controls. The results suggest that a low unsaturated fatty acid diet could be an independent risk factor for ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…As far as cholesterol is concerned, in univariate analysis it appeared that the mean level of cholesterol was higher in cases, but an independent role of hypercholesterolaemia was not shown by our multivariate analysis and, in fact, both cases and controls had mean cholesterol levels within the accepted normal range. It has been suggested that UFA might have an antithrombotic action [3,20,27,28]. Although this action has been ascribed to omega3 acids (which we did not find to differ between cases and controls), a positive effect of oleic acid cannot be ruled out, either by a direct effect or because of a concomitant reduced intake of SFA; in fact, SFA may be important determinants of stroke at the population level [17].…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…As far as cholesterol is concerned, in univariate analysis it appeared that the mean level of cholesterol was higher in cases, but an independent role of hypercholesterolaemia was not shown by our multivariate analysis and, in fact, both cases and controls had mean cholesterol levels within the accepted normal range. It has been suggested that UFA might have an antithrombotic action [3,20,27,28]. Although this action has been ascribed to omega3 acids (which we did not find to differ between cases and controls), a positive effect of oleic acid cannot be ruled out, either by a direct effect or because of a concomitant reduced intake of SFA; in fact, SFA may be important determinants of stroke at the population level [17].…”
Section: Discussionmentioning
confidence: 54%
“…Having described the results of our analysis, some hypothesis on the putative protective effect of UFA on stroke can be suggested [20]: a diet high in UFA might reduce blood pressure and/or reduce cholesterol levels. However, we did not detect any association between 18:1 and hypertension in the various models we tested and showed that both a history of high blood pressure and a diet poor in 18:1 were independent risk factors for ischaemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14] In a prospective study, serum ␣-linolenic acid (an n3 polyunsaturated fatty acid) but not linoleic acid was associated with reduced stroke risk among men at high risk of cardiovascular disease. 15 In that study, the classification of stroke subtypes was not conducted, although the effects of serum fatty acids are likely to differ among stroke subtypes.…”
mentioning
confidence: 99%
“…The degradative process was followed simultaneously by the determination of chemiluminescence and fatty acid composition of brain microsomes. The unsaturation index was used to evaluate the fatty acid alterations observed during the process [14].…”
Section: Introductionmentioning
confidence: 99%